(untitled) (Research, Society and Development, 2021)
The carious disease is present with great frequency in the daily clinical routine of dental surgeons, and is undoubtedly the most prevalent of the lesions. The removal of carious tissue and replacement by restorative materials has long been practiced by these professionals, but the removal method, with the advancement of knowledge, has been replaced, especially by more conservative techniques. Therefore, the aim of this integrative literature review is to gather studies that prove the indication of selective removal, comparing techniques, restorative materials, and success rates. A search was conducted in the PubMed, Scielo and Lilacs databases, using as inclusion criteria: articles that address the proposed subject in Portuguese and English, in full, published in the last 10 years, with descriptors: "dental caries", "selective removal of decayed tissue", "treatment". It can be concluded that the selective removal of decayed tissue brings positive impacts in the management of deep caries lesions, and because it is a simple, minimally invasive technique with promising pulpal results, it has great indications within the philosophy of minimal intervention dentistry.